Pablo García Baena and the Golden Tradition. Gongora's intertext and Cernuda's mediation in three poems of "Fieles guirnaldas fugitivas" - Trabado Cabado, José Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
In this artide we try to examine the intertextual traces in three poems by Pablo García Baena included in the book Fieles guirnaldas fugitivas, Cernuda's influence is studied too as far as the process of recreation of Gongora's works carried out by Pahlo García Baena is concerned. We also study lhe influence of both Gongora and Cernuda on the magazine Cántico and on the rest of García Baena's poetry as an attempt to show the evolulion of Gongorine intertextualiy in the lyrical poetry of García Baena.
Keywords: Pablo García Baena; Luis de Góngora; Luis Cernuda